Gender-leisure nexus through a social justice lens: The voice of women from Iran. (March 2023) - Zarezadeh, Zohreh (Zara); Rastegar, Raymond
Abstract: Leisure is recognised as offering individuals a chance for relaxation, self-development, social interaction, and wellbeing. However, women's participation and experience of leisure in many developing countries are constrained by gender stereotypes and gender-based inequalities. This study aims to investigate the interrelationship of gender, leisure and issues of social justice and equity in the developing country of Iran. This study also demonstrates how constraints to access and participation in leisure activities can further reinforce Iranian women's socioeconomic disadvantage. Twenty-five in-depth interviews were conducted to explore women's narratives of leisure activities and their perceptions of leisure in/equality. The findings reveal that issues such as society norms, cultural mythology and traditions, household and parental responsibilities, personal safety, and crises can restrict women's leisure in Iran. The implications of this study focus on transitional steps for societal changes to reduce marginalisation and bring into being a more inclusive and just society for women. Abstract : We would like to open the discussion by respecting all brave Iranian girls and women who have united in imaginative ways across lines of age, ethnicity, and class to seek their rights.